Exploring Students’ Feedback on the Implementation of Project-Based Learning at English Education of PSDKU MBD - Kamanasa, Louisa Sarah (Koli Journal : English Language Education, 2024)
This study aims to investigate student feedback on project-based learning. The major goal is to investigate the efficacy of project-based learning in improving students' pedagogical expertise. The study involved students from semesters 4 and 6 of the English Education Study Program of PSDKU Unpatti in Southwest Maluku Regency during the academic year 2022/2023. The data collection included eight open-ended questions. Data analysis techniques are utilized at several phases, including data collecting, data presentation, and drawing conclusions. The outcomes from the students' questionnaire are positive feedback about the maximum utilization of time, learning pace, strategic questioning, clarity of presentation, material management, and monitoring for understanding, as well as student engagement during the implementation of the project in class. These findings suggest that integrating project-based learning in 21st-century learning classes is highly effective and suggested for the teaching and learning process.